Role of Mentzer Index for Differential Diagnosis of Iron Deficiency Anaemia and Beta Thalassemia Trait - Shah, Tej Prakash; Shrestha, Anjan; Agrawal, Jagdish Prasad; Rimal, Suman; Basnet, Anita (Journal of Nepal Health Research Council, 2023)
Background: The most common differential diagnoses of microcytic hypochromic anaemia are iron deficiency anaemia and beta thalassemia. Globally, thalassemia affects approximately 4.4 out of every 10,000 live births whereas iron deficiency anaemia comprises half of all anaemia worldwide as per world health organization. The definitive diagnosis of beta thalassemia trait and iron deficiency anaemia requires haemoglobin analysis and iron studies respectively, which are not possible to perform in all suspected cases especially in resource limited settings. The study aims to evaluate the reliability of mentzer index in differentiating beta thalassemia trait from iron deficiency anaemia.Methods: This was a cross sectional, observational study done on 59 patients each of beta thalassemia trait and iron deficiency anaemia from August 2019 to July 2020. Patients who were found to be having iron deficiency anaemia diagnosed by iron studies and beta thalassemia trait diagnosed by Hb electrophoresis were enrolled in the study using simple random sampling technique. Results: Mentzer index correctly identified 95.76% of overall patients. Area under receiver operating characteristic curve was 0.993 (95% CI, 0.985-1.002, p<0.001). For beta thalassemia trait, mentzer index showed a sensitivity of 93.2%, specificity of 98.3%, positive predictive value of 98.2%, negative predictive value of 93.5%; while for iron deficiency anaemia, sensitivity of 98.3%, specificity of 93.2%, positive predictive value of 93.5% and negative predictive value of 98.2%. Youden’s index was 91.5.Conclusions: The findings of the present study make mentzer index a reliable screening method, especially in a resource poor setting, like Nepal. Further confirmation by gold standard tests is recommended.Keywords: Beta thalassemia trait; iron deficiency anaemia; mentzer index